-7x+7-3x=67

Simple and best practice solution for -7x+7-3x=67 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7x+7-3x=67 equation:


Simplifying
-7x + 7 + -3x = 67

Reorder the terms:
7 + -7x + -3x = 67

Combine like terms: -7x + -3x = -10x
7 + -10x = 67

Solving
7 + -10x = 67

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + -7 + -10x = 67 + -7

Combine like terms: 7 + -7 = 0
0 + -10x = 67 + -7
-10x = 67 + -7

Combine like terms: 67 + -7 = 60
-10x = 60

Divide each side by '-10'.
x = -6

Simplifying
x = -6

See similar equations:

| 6x+6+4x=-44 | | 0.4x+x+30+0.6x+x=360 | | cx+d=20 | | 20r^2-16r=48 | | 864x-x^2-176015=0 | | -19X=228 | | -3X=-81 | | -37.9N=303.2 | | 19.2R=115.2 | | 563x-0.5x^2-142104=0 | | -6+S=10 | | .80(d-100)=450 | | 1.7=3y+12.8 | | d-50=.80(d-100) | | 914x-x^2-191949=0 | | 17X-10X= | | 5y^2+24y-36=0 | | -7.2(m-3)+m=21.6 | | -16k=204 | | -15X-10Y+5= | | 2x^2=15x-25 | | 23=y-6 | | (2x^2)-27=0 | | -4x-23=-83 | | (2x^2)=0 | | 6s+11s=51 | | 8x+13x= | | -9d=135 | | 279-4x=41x+24 | | 12m=48 | | -26-8x=59-22x | | 4y=3x-8 |

Equations solver categories